Pengembangan Perangkat Pembelajaran dengan Model Think Pair Share (TPS) Pada Mata Pelajaran IPA - Pande Putu Rizky Ari Pratana; Ndara Tanggu Renda; Ni Wayan Arini (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
Learning is still dominated by teachers using lectures and teacher learning tools are still not good. This study aims to produce learning tools in the form of lesson plans with the think pair share (TPS) model in the science subject with the theme Kayanya Negeriku for fourth-grade elementary school. This research is development research based on the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation, due to time constraints. and conditions that do not support this research only to the development stage. The results of the analysis of the development of learning devices with the think pair share (TPS) model obtained the following results: the content validity of the instrument was 1, 00 with the interpretation of "very high", the reliability of the instrument obtained a practicality coefficient of 100%, and the validation of learning devices with an average of 4,67 with "very good" interpretation. Based on the results of the study, it can be concluded that the validity of the Development of Learning Devices with the Think Pair Share (TPS) Model in the Science Subjects of Kayanya Negeriku Theme Class IV Elementary School is declared valid and suitable for use in the learning process.